Nursing workload in an intensive care unit and its relation with nosocomial infection incidence - Rosana Alameda Varela; Isabel Cerrillo González; Sonia García Gómez; Gloria Rollán Rodríguez; Cristina Quirós Herranz; Montserrat Martínez Lareo; Francisco Javier Carmona Monge; Ana Jara Pérez (Fundación para el Desarrollo de la Enfermería, 2011)
Nosocomial infection is one of the most common causes of adverse events and complications related to health care. Development of nosocomial infection is associated with an increase in hospital stay and mortality and an overall increase in health care costs. Knowing the incidence of nosocomial infection is an effective way of controlling and preventing it. Identifying the relationship between nursing workload and nosocomial infections in critical care may be helpful to adjust the staff to the real requirements of the intensive care unit and may help reducing costs. The aim of the present study is to analyze the influence of nursing workload in the development of nosocomial infections in patients admitted to an intensive care unit. A longitudinal correlational research will be performed. The sample will be comprised of the patients admitted in the intensive care unit of the Hospital Universitario Fundación Alcorcón.Data regarding sociodemographical variables, ventilador-associated pneumonia, intravascular catheter location and duration, urinary catheter type and duration, and all pertinent cultures will be obtained from the medical records. Nursing Activities Score scale will be used to assess daily nursing workload in the unit. The number of patients admitted daily, as well as the number of nursing professionals working in each shift will also be taken into account.